Predictors, neuroimaging characteristics and long-term outcome of severe european tick-borne encephalitis: a prospective cohort study - Lenhard, Thorsten; Ott, Daniela; Jakob, Nurith Juliane; Pham, Mirko; Bäumer, Philipp; Martinez Torres, Francisco Javier (PLOS ONE, 2016)
Background and Objectives Tick-borne encephalitis (TBE) still represents a considerable medical and health economic problem in Europe and entails a potential threat to travellers. The aim of this study was to characterise the conditions of severe TBE by precisely recording its clinical variants, the related neuroimaging features, and the variant-specific long-term outcome and by identifying predictors for severe courses. Methods A cohort of 111 TBE patients (median age 51, range 17-75 years; 42% females) was analysed prospectively. Data were acquired from the department of neurology, University Hospital Heidelberg, and the infectious diseases registry of the Robert-Koch institute Berlin. Neurological status was ascertained by protocol at admission and discharge and the degree of disability was scored using the modified RANKIN Scale (mRS; clinical score addressing neurological disability, range from 0, healthy to 6, dead) at admission and at follow-up. Follow-up examination was conducted by means of a telephone interview. To identify independent predictors for severe TBE and functional outcome, modelled logistic regression was performed. MRI changes were correlated with infection variants. To assess alpha-motor neuron injury patterns, we used high-resolution magnetic resonance neurography (hrMRN). Analyses were performed at the Department of Neurology, University Hospital, University of Heidelberg from April 2004 through September 2014 Results Acute course: 3.6% of patients died during the acute infection. All patients with a lethal course suffered from meningoencephaloradiculitis (MER, 14.4% of the cohort), which is associated with a significantly higher risk of requiring intensive care (p = 0.004) and mechanical ventilation (p<0.001) than menigoencephalitis (ME, 27.9% of the cohort). At admission, both MER and ME groups were severely affected, with the MER group having a statistically higher mRS score (median of 5 in the MER groups versus 4 in the ME group; p<0.001). Long-term outcome: outcome for MER was considerably worse (median mRS = 4) than for ME (mRS = 1, p<0.0001) and meningitis (mRS = 0, 57.7% of the cohort). Risk factors: advanced age (p<0.001) and male gender (p = 0.043) are independent risk factors for a severe infection course. Furthermore, we identified pre-existing diabetes mellitus (p = 0.024) as an independent risk factor for MER. In MER, alpha-motor neuron injury accounts for the poor prognosis confirmed by hrMRN. Conclusion and Relevance These data provide critical information for neurologists and other health professionals to use in evaluating TBEV patients who live in or travel to endemic areas. This information can be used to classify clinical presentation and estimate infection-associated complications and individual prognosis. Furthermore, the risk for severe, disabling infections in older patients should prompt general practitioners to recommend and encourage vaccination to those patients living in or travelling to endemic areas.